«Капелюх Сікорського» В. Даниленка: шлях від ідеографічного до символічного функціонування образів (Literatures of the World: Poetics, Mentality and Spirituality, 2016)
The portraits of Karolina Huliy and Ihor Sikorsky in V. Danylenko’s novel «Sikorsky’s hat» while fulfilling their main function of creating the images of fiction and real character through the description of appearance and deepening into their inner world, psychology of action and deeds, accumulate the diversity going through the widening from the ideographic to symbolic (the woman with a propeller) functioning of the images. Karolina’s portrait forms metaphoric and symbolic meaning of the literary work saving from oblivion herself and another main hero, adding dynamics to the plot development.
Keywords: biography; portrait; detailed portrait; deconcentrated portrait; oneiric portrait